Relationship between the duration of injectable contraceptive Depo Medroxy Progesterone Acetat (DMPA) With the Occurrence of Amenorrhea in Family Planning Acceptors at the Pratama Delima Rahayu Clinic, Sragen - Venesia Manek, Elisabeth; Prastyoningsih, Aris; Bumi Pangesti, Christiani (Journal of Advanced Nursing and Health Sciences, 2024)
Amenorrhea is a condition where a person does not experience menstruation for 3 to 6 months in a row. This research aims to analyze the relationship between length of use of injectable contraceptives Depo Medroxy Progesterone Acetat (DMPA) with the occurrence of amenorrhea in family planning acceptors at the Pratama Delima Rahayu Clinic, Sragen Indonesia. This type of analytical survey research uses a cross sectional approach. The sampling technique for this research is to use a total sampling technique, namely the entire population. The results of the research show that the length of use of the Depo Medroxy Progesterone Acetate (DMPA) contraceptive injection has a significant relationship with the occurrence of amenorrhea in contraceptive acceptors at the Pratama Delima Rahayu Sragen Clinic with a probability value of 0.001 < 0.05. The conclusion from this research is that the longer you use DMPA injection contraceptives, the longer you will experience menstrual disorders, one of which is amenorrhea.